Marine Spatial Planning: International Law Perspective - Elvira F. Pushkareva (Московский журнал международного права, 2014)
This paper is devoted to the international law regulations of marine spatial planning, including the concept of marine spatial planning and current international cooperation in the field. More specifically, the research suggests recommendations on cooperation between Russia and Norway on managing the Barents Sea resources.